GE_GERICHTE A/391/2023 vom 13. Februar 2025 - GE Cour de justice (2025)
ZONE AGRICOLE;REMISE EN L'ÉTAT;OBJET DU LITIGE;PRINCIPE DE LA BONNE FOI;PROPORTIONNALITÉ | LAT.22; LCI.1; RCI.1; LCI.129; LCI.130; Cst.5.al2; Cst.9